2018
DOI: 10.1177/1534508418771739
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the Effectiveness and Interactions of Instructional Coaches: Initial Psychometric Evidence for the Instructional Coaching Assessments–Teacher Forms

Abstract: The conceptual foundation and initial psychometric evidence are provided for the Instructional Coaching Rating Scales and Interaction Style Scales–Teacher Forms. These forms are part of a multicomponent online assessment system designed to evaluate the effectiveness of coaching skills and interactions that support the needs of teachers and students. Specifically, the article presents the theory, evidence, and measurement framework for the system. Findings indicate that the Rating Scales and Interaction Style S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Elementary school teachers stated that school principals, supervisors, colleagues from both the same elementary school and peers from different elementary schools has a role for them to improve their abilities even though it is not optimum yet (Ndibalema, 2019). The interaction between teachers and peers in the TWG is very useful to develop their abilities so that they can carry out assessments to measure the mastery of the concept of inquiry-based science in elementary schools (Reddy, Glover, Kurz, & Elliott, 2019). The competency of school principals/ supervisors who are directly related to the implementation of learning in elementary school influences the readiness to be able to prepare the inquiry-based science problem well in elementary schools.…”
Section: Resultsmentioning
confidence: 99%
“…Elementary school teachers stated that school principals, supervisors, colleagues from both the same elementary school and peers from different elementary schools has a role for them to improve their abilities even though it is not optimum yet (Ndibalema, 2019). The interaction between teachers and peers in the TWG is very useful to develop their abilities so that they can carry out assessments to measure the mastery of the concept of inquiry-based science in elementary schools (Reddy, Glover, Kurz, & Elliott, 2019). The competency of school principals/ supervisors who are directly related to the implementation of learning in elementary school influences the readiness to be able to prepare the inquiry-based science problem well in elementary schools.…”
Section: Resultsmentioning
confidence: 99%
“…There are also a multitude of specific instructional strategies that promote learning across contexts, such as supporting learning through questioning techniques, providing specific academic and behavioral feedback (praise, correction), providing varying modalities for learning and different assessments of knowledge, and relating content to prior learning and real-world experience (Allington, 2002;Kamil et al, 2008;Kazemi & Stipek, 2009;Pianta & Hamre, 2009;Stronge et al, 2011). A key aspect of "effectiveness" has long been regarded as a teacher's ability to seamlessly and consistently implement instruction and positive management practices across lessons and adapt practices based on student needs and instructional context (Reddy, Glover, Kurz, & Elliott, 2019;Stronge, 2008). Presently, there are several published measures that strive to capture various aspects of the aforementioned elements of teaching effectiveness (warmth, rigor, classroom management, and instructional strategies) through classroom observations or student ratings (Ferguson & Danielson, 2013;Pianta & Hamre, 2009).…”
Section: Elements Of Effective Teaching Practicementioning
confidence: 99%
“…Furthermore, they reported data in which specific coaching actions were predictive of student outcomes on end-of-year assessments. Reddy, Glover, Kurz, and Elliott (2019) focused their study on Path C (see Figure 1) by conducting the initial investigation of the utility and validity of a teacher completed assessment of instructional coaching (i.e., Instructional Coaching Assessments–Teacher Forms ). Reliability indicated that the assessment demonstrated high internal consistency and data suggested the measure is relatively free from item bias.…”
Section: Studying the Complex Systems Of Teacher Practicementioning
confidence: 99%
“…Interestingly, their tool allowed the research team to analyze which specific coaching behaviors (i.e., providing feedback, structuring practice) were associated with change in teacher and student outcomes. Relatedly, Reddy et al (2019) explored the technical adequacy of an assessment that allows researchers to collect data on teachers’ perceptions on the effectiveness of instructional coaching. Combined, both studies contribute to understanding of important aspects of the coach–teacher relationship that are critical to understanding teachers’ implementation of interventions and associated gains in student outcomes.…”
Section: Future Directionsmentioning
confidence: 99%